Financial effectiveness and productivity of the agricultural sector in Poland - Wojciech Misiąg; Tomasz Skica; Jacek Rodzinka (Financial Internet Quarterly, 2020)
Agriculture is neither the largest nor the most effective segment of the Polish economy. However, since its importance goes beyond purely numerical characteristics, it is justified for the State to support it. What is important in this regard, however, is a kind of balance. These measures cannot be a substitute for initiatives to strengthen its financial efficiency and increase its productivity. The key question therefore becomes to what extent agricultural support through financial instruments improves the performance of this sector of the Polish economy and how neutral it remains for it, while burdening public finances. In view of the above, the purpose of this article is to examine the productivity and financial efficiency of agriculture in Poland using the FADN methodology based on agricultural accounting. The structure of the article has been subordinated to the achievement of the intended research objective. The article starts with an introduction to the issues of financial efficiency and productivity in agriculture. Next, there is a presentation of agriculture and its characteristics as a segment of the Polish economy. Further presented and discussed are the data and methodology used in the study and studies on the productivity and financial efficiency of agriculture in Poland. In the final part of the article, the authors seek to analyse the impact of public transfers on market effects and discuss the modernisation of Polish agriculture and improvement of rural infrastructure. In a sense, the whole analysis closes with a summary containing the most important findings of the studies carried out.
Keywords: R51; Q14; Q19; D24; 330; financial efficiency of agriculture; FADN accounting; agricultural productivity